GENDER DIFFERENCE IN MATHEMATICS PERFORMANCE AMONGST SENIOR HIGH SCHOOL STUDENTS IN THE UPPER WEST REGION (UWR), GHANA - Mohammed Yikehere Marifa; Johnson Michael Nabie; Joshua Kai Dossey (Kalamatika)
Gender differences in mathematics performance have long concerned parents and policymakers in Ghana, especially in the UWR. This study examined these differences among high school students using an explanatory sequential mixed-methods design. Stratified and Simple Random Sampling techniques were used to sample 350 participants from four different SHS within the UWR to participate in the survey whilst four teachers were selected using the purposive sampling technique. A mathematics test, questionnaires, and interviews were the main data collection tools. Quantitative data were analysed using descriptive and inferential statistics, while qualitative data were analysed thematically. The results reveal no statistically significant difference between female and male mathematics performance [t(348)= -1.44, p =.153, p>.05]. Also, factors such as societal expectations and stereotype threat, cultural norms, learning environment, and teaching methods were indicated as potentially contributing to female and male mathematics performance. It was recommended that an all-inclusive learning environment, teaching practices, and curriculum design should be created to allow students, regardless of their gender, to participate effectively in mathematics classes.